Facile template synthesis of dumbbell-like Mn2O3 with oxygen vacancies for efficient degradation of organic pollutants by activating peroxymonosulfate. Issue 3 (14th January 2020) - Li, Yang; Li, Didi; Fan, Shisuo; Yang, Ting; Zhou, Qi
Abstract : A novel dumbbell-like Mn2 O3 microstructure prepared under mild conditions was used as a catalyst to PMS activation for RhB degradation. In the Mn2 O3 /PMS system, the reactive oxygen species were revealed in the degradation process by PMS activation. Abstract : In this work, novel dumbbell-like Mn2 O3 was prepared using a low-cost and environmentally friendly template (gelatin) and applied to activate peroxymonosulfate (PMS) for pollutant degradation. The characterization results showed that dumbbell-like microstructures were formed by the self-assembly of tiny nanoparticles. Mn2 O3 -G (gelatin as the template) as a heterogeneous catalyst for PMS activation could effectively degrade various pollutants and exhibited an excellent degradation rate of rhodamine B (0.2333 min −1, in 30 min) for PMS activation compared to Mn2 O3 -C (carboxymethyl cellulose as the template), Mn2 O3 -N (without a template), and MnO2 . The superior catalytic performance of Mn2 O3 -G was ascribed to its high oxygen vacancy content. The radical scavenging and EPR experiments revealed that SO4 ˙ −, OH˙, O2 ˙ −, and 1 O2 were identified as reactive species generated from PMS activation. The oxygen vacancies participated in the generation of the reactive species. Thus, a facile and environmentally friendly method is provided for the synthesis of dumbbell-like Mn2 O3 as a high-efficiency catalyst for PMS activation. Furthermore, this study shows a new mechanistic insight into PMS activation on Mn2 O3 .